An Analysis of Earnings Management in India: An Empirical Study - Kaushal, Monalisa (Indian Journal of Finance, 2013)
Using a sample of 1,035 company year observations for the years 2006 to 2010, an effort has been made in the present study to assess the magnitude of earnings management through accruals estimation. The study investigates the overall breadth and scope of earnings management behavior in a broader context through a comprehensive analysis of reported earnings across Indian industry sectors and individual company characteristics. The results affirmed that earnings management as depicted by discretionary accrual exists in the Indian companies. The results provide some evidence to the fact that earnings management has an unfavourable effect on the value of the company.